QUALITY CHARACTERISTICS OF CURED FISH OF COMMERCE - KALAIMANI, N; GOPAKUMAR, K; NAIR, T.S UNNIKRISHNAN (Fishery Technology, 2017)
A survey was conducted at the fish curing yards at Shakthikulangara (Quilon), fish market at Vizhinjam, fish curing yards, fish market as wen as dry fish godowns in and around Tuticorin. A total of 23 samples of different varieties of fishes collected from the markets and curing yards and 8 samples of anchovies collected from different godowns at Tuticorin were analysed to evaluate the quality and extent of fungal and insect infestation. Samples were analysed for proximate composition and estimated their water activity. About 70 % of the 23 samples of different varieties of fish were found to be unfit for consumption and 12.5 % of the samples of anchovies were found to be infested with beetle, after 3 weeks of storage after collection from these centres.